PUTREN VILLAGE DEVELOPMENT STRATEGY FOR IMPROVING THE VILLAGE DEVELOPMENT INDEX (IDM) STATUS - Krisna Agung Brah Murti; Linda Dwi Rohmadiani (PT. Jurnal Center Indonesia Publisher, 2026)
Based onthe conditions of the Village Development Index (IDM) for Putren Village, usingscoring analysis in 2023, the score was 0.694, with a detailed Social Resilience Index (IKS) score ofSocial Resilience Index (IKS) is 0.748, the Economic Resilience Index (IKE)is 0.667, and the Environmental Resilience Index (IKL) is 0.667. With this IDM score, Putren Villageis classified as a developing village because it has not yetoptimized its Economic Resilience Index and Environmental Resilience Index.This study aims to formulate a development strategy for Putren Villagetowards becoming an independent village based on the IDM. The analysis method applied inthis study is descriptive qualitative through content analysis. Thedata collection methods used are questionnaires and interviews. The results of the analysisshow that the development strategy for Putren Village towards becoming an independentvillage based on IDM criteria and community expectations is directed at the developmentand repair of village roads, the provision of integrated drainage, the formation of BUMDesand the improvement of the competence of the community